Aplica????o modelo integrativo e mensura????o de lealdade em relacionamento B2B - business to business: uma aplica????o no setor de medicina diagn??stica - Perp??tuo, Fl??vio de Carvalho (2016)
Diagnostic medicine is a specialty aimed at performing complementary tests to aid diagnosis, with impact on the different stages of the health chain: prevention, diagnosis, prognosis and therapeutic follow-up. Official sources of the public sector ??? DATASUS (Brazilian Health System Database) and the private sector - ANS estimate that the sector handled R$ 33.24 billion in the year 2015. The purpose of this study is to evaluate the relationship between the definition criteria of outsourcing diagnostic services with Loyalty theory, based on a structural model that portrays, at the consumer level, the relationships of attitudinal and behavioral loyalty with constructs of Loyalty Background: Satisfaction, Trust, Perceived Value, Quality, Cost of Change and Perceived Justice. The main objective of the Research is the Application of Integrative Model for measuring the constructs of Loyalty Background in the B2B relationship in the diagnostic medicine sector. In order to direct the accomplishment of the study, the following main research question was posed: what antecedents are relevant in the construction of Loyalty in B2B relationships in the Diagnostic Medicine Sector? The empirical study can be classified as a quantitative, descriptive survey carried out in cross-section and structured in a strategy of analysis by action research. The present research proposes to study the influence of the antecedents of consumer loyalty. The study collected information from clients for the construction of a theoretical model that was analyzed through the modeling of structural equations and the partial least squares (PLS) technique. The theoretical framework used included relationship marketing and recognized antecedents of consumer loyalty. The results demonstrated the consumers' understanding of the judgment of the results received, mainly the positive influence of this evaluation on their satisfaction as an important aspect for the construction of their loyalty to the supplier.